Issues and challenges faced by government office buildings in performing maintenance work - Ali, A.S.; Chua, S.J.L.; Ag Ali, D.B. (Penerbit UTM Press, 2016)
In Malaysia, most of the building managers faced problems in conducting maintenance operation due to unclear plan and unsystematic approach. Improper maintenance management and practices could affect the performance levels of the maintenance works and the productivity of the building users. This paper aims to examine the issues and challenges faced by government office building managers in selecting an appropriate maintenance strategies. This study adopted mixed method which is a combination of both qualitative and quantitative methods. Three government office buildings in Kota Kinabalu, Malaysia were selected as the case study. Structured interviews were conducted with the building maintenance managers and 200 questionnaires were distributed to the buildings occupants. A total of 67.5% questionnaires were valid for data analysis. The results showed that there are significant correlation between the frequency of services breakdown and the productivity of the building user. Top management, human resource and technical problems were identified as the issues and challenges faced by building managers in conducting maintenance work. Based on the data obtained, the performance level of building maintenance services are analysed using three selected performance indicators. From the findings, it is proven that the issues and challenges faced affect the performance levels of the maintenance works. In contrast, if the building managers do not face too many issues and challenges in implementing the maintenance works, the maintenance strategies will perform in an optimum level.